THE INFLUENCE OF WORK CULTURE VALUE ON OFFICIAL'S PERFORMANCE AT PT BANK BUKOPIN Tbk OF MAIN BRANCH OFFICE OF MAKASSAR - Mursalim Nohong; Wardhani Hakim; Ahmad Salihin (Scientia Integritas Utama, 2023)
This research aims to find out the influence of the working culture values ​​of Bank Bukopin involving professionalism, integrity, customer orientation, continuous improvement at PT. Bank Bukopin Tbk. of Main Branch Office of Makassar, and find out the more dominant value affecting officials' performance at PT. Bank Bukopin Tbk. of Main Branch Office of Makassar. The population in this research consists of 103 officials. The sample consisted of 84 officials selected using Isaac and Michel formula with a deviation level of 5%. The data consists of primary and secondary data obtained through a questionnaire and documentation technique. They were then analyzed using validity and reliability analyzes to test the hypothesis. They were processed using the SPSS program version 14.00 The results of multiple regression analysis show that the culture values ​​of Bank Bukopin involve professionalism, integrity, focus for customer orientation, continual improvement have influence on officials' performance. The results of the analysis indicate that the dominant value affecting official performance is continuous improvement. This is shown by regression analysis in which t-count is 2.652 and the amount of contribution of working culture value to officials' performance is 58.2%, while the rest 41.8% is influenced by other variables which are not under research.